Az aranykor vége: A kockázati- és magántőke-ágazat fejlődése Közép- és Kelet-Európában - Judit Karsai (Hungarian Academy of Sciences, Institute of Economics, 2008)
– The current downturn in the American and Western European economies, combined with increasing regulatory pressure on private equity throughout the developed world, made emerging markets an attractive destination for private equity. As part of the emerging markets, Central and Eastern Europe's (CEE) private equity industry was an accidental beneficiary of this development. The attractiveness of the CEE markets was also boosted by the fact that value added resulted from the organic growth of the companies, rather than from leverage utilisation. As a result of the crisis in autumn 2008, the growth financed by loans itself became a synonym of the risk. Consequently the CEE countries as parts of emerging markets were handicapped, irrespective of the already applied greatest cautiousness of investors and the relatively deteriorated availability and higher interest rates of provided loans in the region. Since the majority of high volume capital raised recently by private equity funds in the CEE region still expected to be invested, it is not likely that the cutback of private equity financing in the CEE countries will be as radical as it was in the developed markets. The Golden Age of the private equity investments in the CEE region, however, ended in the autumn of 2008. The paper forecasts the future developments of the private equity industry in the CEE region, based on a detailed analysis of the five years' tendencies. The paper reviews within an international surrounding the changes in the volume and structure of raised regional funds, as well as the actual investment trends by the related countries and sectors. The study provides several examples for the applied individual corporate level investments strategies of private equity investors in the CEE region. The chosen exit routes and returns received by regional private equity investors are also illustrated with actual examples. The final part of the analysis speculates on the future effects of the global financial crisis and recession on the private equity industry of the CEE region.
Keywords: G23; G24; G34; M13; 330; Venture Capital; Private Equity; Central Eastern Europe (CEE); International Asset Allocation; Institutional Investors; Merger & Acquisition; Corporate Restructuring; Risikokapital; Private Equity; Osteuropa